Examen especial del manejo de inventario y su incidencia en el patrimonio de la empresa PRODUVET del cantón Santo Domingo, Provincia de los Tsáchilas, año 2012 - Montiel Jacome, Jorge Enrique (2015)
This research was executed in the Province of Santo Domingo de los Tsáchilas, Canton Santo Domingo, in the company PRODUVET located on the street Portoviejo s / n between Ibarra and Latacunga. Whose general objective is to run a special review of inventory management and its impact on the equity of the company PRODUVET the canton Santo Domingo province of Tsáchilas, 2012. The methods and types of research were: type of field research and methods are inductive and deductive; Transversal. For the realization of this research was taken as sources, data provided by the company Produvet. As is the Manager, Chief Accountant and cellar. Once done the respective risk analysis in relation to the inherent risk and detection, in which it was determined that the company PRODUVET, which represents a 29.50% determining it a low risk. To perform inventory lifting a formula was applied to a population of 1,214 items; which was taken as reference 92 split to the four existing product lines in the company which are: agricultural, veterinary, fertilizer and farm equipment, resulting in 23 to evaluate product line. The product line has the greatest volume is 32% agricultural products; fertilizer at 31%; veterinary with 27% and agricultural machinery with 10%. Once completed the following audit findings Lack of administrative policies within the company raised PRODUVET: Unlimited experience in inventory management and proper comparison in the enterprise system PRODUVET; Weak inventory control inventory against loss, theft, damage system.